Karen Eichel: capstone - Eichel, Karen, artist (Colorado State University. Libraries, 2013)
The artist's statement: "We tell those things that we feel have a chance poetically of fitting back into life. That means fitting back into the feelings of other people." - Emmet Gowin. I am inspired by the people around me. These photographs are simply my own experiences of life. The action of photographing a person allows others to see aspects, features, and characteristics about a person that create comparisons and evoke emotions within the viewer allowing them to relate the images to their own life, and the people around them. Through these images I explored my own experiences, and the time of which I am living my life at this very moment. All of these images address a unique time period in a person's life; the time of young adulthood; a unique time period that is ever changing. Each photograph captures a moment in time that will never be again for that person or for us as a viewer to experience. It only exists as an image. All prints are Color Projection Prints $225 Framed $150 Print Only.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a self-assessment paper, and images of works.